Genomic and ecological divergence support recognition of a new species of endangered Satyrium butterfly (Lepidoptera, Lycaenidae) - Zachary G. MacDonald; Julian R. Dupuis; James R. N. Glasier; Robert Sissons; Axel Moehrenschlager; H. Bradley Shaffer; Felix A. H. Sperling (ZooKeys)
We describe a highly isolated population of hairstreak butterfly from Waterton Lakes National Park, Alberta, Canada, as a new species, Satyrium curiosolus sp. nov., previously recognized as Satyrium semiluna (Half-moon Hairstreak). We propose “Curiously Isolated Hairstreak” as the common name due to its disjunct and unusual distribution. Previous whole-genome analyses revealed S. curiosolus has extremely low genomic diversity and is highly divergent from the nearest S. semiluna populations in British Columbia and Montana, more than 400 km distant. Further analysis suggested prolonged inbreeding and isolation for up to ~40,000 years BP. Ecological niche modeling indicated that S. curiosolus occupies environmental conditions that are distinct from S. semiluna, suggesting niche divergence driven by long-term geographical and ecological separation. While host plant and ant associations have not been definitively resolved, they likely differ between S. curiosolus and S. semiluna. As part of this description, we provide whole-genome consensus sequences for each individual of the type series and identify 21,985 single nucleotide polymorphisms (SNPs) that are divergently fixed between S. curiosolus and S. semiluna, including 117 unlinked SNPs distributed across the genome as putative diagnostic markers. Previously listed as Endangered in Canada as the Waterton population of S. semiluna, S. curiosolus should retain this conservation status due to its extreme isolation, small population size, and flatlined genomic diversity. We propose species recognition as a testable hypothesis under the General Lineage Concept and recommend further research to explore the taxonomy, ecological relationships, and conservation of the greater species complex, including S. curiosolus, S. semiluna, and S. fuliginosa.